2013
DOI: 10.1103/physrevlett.111.266401
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic Melting Transition of a Soliton Lattice in a Commensurate Charge Modulation

Abstract: We report on the observation of the hysteretic transition of a commensurate charge modulation in IrTe 2 from transport and scanning tunneling microscopy (STM) studies. Below the transition (T C ≈ 275 K on cooling), a q ¼ 1=5 charge modulation was observed, which is consistent with previous studies. Additional modulations [q n ¼ ð3n þ 2Þ −1 ] appear below a second transition at T S ≈ 180 K on cooling. The coexistence of various modulations persists up to T C on warming. The atomic structures of charge modulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
102
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(118 citation statements)
references
References 30 publications
14
102
1
Order By: Relevance
“…One can notice gradual increase of the peak intensity in heating, especially from 200 to 280 K, mainly due to improvement of the modulation regularity. An additional 1/11 ordering of a minor faction was observed in LT phase in the scanning tunnelling microscope (STM) 19 . However, any hint of this order is not observable in the XRD, indicating that it is a surface phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…One can notice gradual increase of the peak intensity in heating, especially from 200 to 280 K, mainly due to improvement of the modulation regularity. An additional 1/11 ordering of a minor faction was observed in LT phase in the scanning tunnelling microscope (STM) 19 . However, any hint of this order is not observable in the XRD, indicating that it is a surface phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identify with STM a unprecedented honeycomb charge ordering in nanoscale coexistence with stripe charge orders of IrTe2 [19][20][21][22][23][24] , which is distinct from the hexagonal CDW.…”
mentioning
confidence: 99%
“…IrTe2 is currently under extensive investigations due to its unusual electronic properties related to the charge ordering. IrTe2 is an outstanding transition metal dichalcogenide with a charge order (Ir 5d 3+ -Ir 5d 4+ ) transition into 4 stripe phases with a large hysteresis and a nontrivial remnant metallic conductivity [19][20][21][22][23]25,26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both the HT and LT phases of IrTe 2 show significant threedimensional electronic structures reflecting interactions (and in the case of the LT phase, bonding) between adjacent CdI 2 structure layers, which is very different from most layered dichalcogenides, which are generally more two dimensional and show real CDW instabilities 10 . Several scanning tunnelling microscope (STM) studies 11,12 have been reported recently on IrTe 2 , but the relationship between the structural and electronic properties remains to be fully elucidated. In any case, the fact that the transition is associated with Te-Te bonding with interlayer bonds suggests that the surface may favour a different pattern than the bulk leading to a competition.…”
mentioning
confidence: 99%